Moringa Leaf Powder Utilization in Feed to Improve the Egg Quality of ISA Brown Chickens - Riyanti, Riyanti; Septinova, Dian; Nova, Khaira; Tantalo, Syahrio; Urba, Musyarofah Rahmah; Salsabilla, Annisa; Hasiib, Etha 'Azizah (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
Innovation or nutritional engineering in the process of raising laying hens to produce eggs as a functional product is really needed by society. The specific objective to be achieved is to optimize the use of Moringa oleifera leaf flour in improving the quality of eggs. The research method was carried out experimentally using a completely randomized design, consisting of three treatments of moringa leaf flour (Moringa oleifera) supplementation at 1%, 2% and 3%. Each treatment was repeated six times and each repetition used 9 Isa Brown 73 weeks laying hens. The variables observed included egg weight, albumen index, yolk index, yolk color and Haugh Unit score. The research results showed that supplementation of 1-3% Moringa oleifera leaf flour in the diet produced relatively the same egg weight, albumen index, yolk index, yolk color and HU score